ANALYSIS OF THE APPLICATION OF THE FIXED ASSETS DEPRECIATION METHOD REVIEWED FROM THE POINT OF FINANCIAL ACCOUNTING STANDARDS (SAK) AND TAXATION - Simanjuntak, Rudyanto; Leoni Ginting (PT. MITRA ANGKASA INFORMATIKA, 2024)
Analysis of the Application of Fixed Assets Depreciation Method from the perspective of Financial Accounting Standards (SAK) and the taxation law. The results show that the company has implemented in this case the statement of financial accounting standards No. 16 which has